The impact of HIV infection and disease stage on the rate of weight gain and duration of refeeding and treatment in severely malnourished children in rural South African hospitals - Moïse Muzigaba; Benn Sartorius; Thandi Puoane; Brian Van Wyk; David Sanders (South African Medical Association, 2017)
Background. Evidence of the effects of HIV infection and clinical stage on the duration of refeeding and treatment (DRT) and the rate of weight gain (RWG) in severely malnourished children remains inconclusive. Objectives. To determine whether the RWG and DRT differ by baseline clinical characteristics, and to assess the effect of HIV status and disease stage on the relationship between these two clinical outcomes. Methods. This was a retrospective record review of 346 patiens discharged between 2009 and 2013 following treatment for severe acute malnutrition (SAM) at two rural hospitals in South Africa. Results. A third of the sample was HIV-positive, the RWG (measured as g/kg/day) was significantly slower in HIV-positive patients compared with HIV-negative cases (mean 5.2, 95% confidence interval (CI) 4.47 - 5.93 v. mean 8.51; CI 7.98 - 9.05; p<0.0001) and cases at stage IV of HIV infection had a significantly slower RWG (mean 3.97; CI 2.33 - 5.61) compared with those at stages I (mean 7.64; CI 6.21 - 9.07) (p<0.0001) and II (mean 5.87; CI 4.74 - 6.99). The mean DRT was longer in HIV-positive cases and those at advanced stages of HIV infection. HIV-positive cases were renourished and treated for almost 3.5 times longer than their HIV-negative counterparts to achieve a moderate RWG (5 - 10 g/kg/day). Conclusion. This study highlights the need to reconsider energy requirements for HIV-positive cases at different clinical stages, for more rapid nutritional recovery in under-resourced settings where prolonged hospitalisation may be a challenge.